Normal distribution pattern and physiological variants of 68Ga-PSMA-11 PET/CT imaging. Issue 11 (November 2016) - Demirci, Emre; Sahin, Onur Erdem; Ocak, Meltem; Akovali, Burak; Nematyazar, Jamal; Kabasakal, Levent
Abstract : Purpose: 68 Ga-PSMA-11 is a novel PET tracer suggested to be used for imaging of advanced prostate cancer. In this study, we aimed to present a detailed biodistribution of 68 Ga-PSMA-11, including physiological and benign variants of prostate-specific membrane antigen (PSMA) imaging. Materials and methods: We carried out a retrospective analysis of 40 patients who underwent PSMA PET/computed tomography (CT) imaging and who had no evidence of residual or metastatic disease on the scans. In addition, 16 patients who underwent PSMA PET/CT imaging with any indication other than prostate cancer were included in the study to evaluate physiological uptake in the normal prostate gland. The median, minimum–maximum, and mean standardized uptake value (SUV) values were calculated for visceral organs, bone marrow and lymph nodes, and mucosal areas. Any physiological variants or benign lesions with 68 Ga-PSMA-11 were also noted. Results: 68 Ga-PSMA-11 uptake was noted in the kidneys, parotid and submandibular glands, duodenum, small intestines, spleen, liver, and lacrimal glands, and mucosal uptake in the nasopharynx, vocal cords, pancreas, stomach, mediastinal blood pool, thyroid gland, adrenal gland, rectum, vertebral bone marrow, and testes. Celiac ganglia showed slight 68 Ga-PSMA-11 uptake in 24 of 40 patients without the presence of any other pathologic lymph nodes in abdominal and pelvic areas. Variable uptake of 68 Ga-PSMA-11 was observed in calcified choroid plexus, a thyroid nodule, an adrenal nodule, axillary lymph nodes and celiac ganglia, occasional osteophytes, and gallbladder. The patient group with PSMA PET/CT for indications other than prostate cancer ( n =16) showed a slight radiotracer uptake in normal prostate gland (SUVmax : 5.5±1.6, range: 3.5–8.3). Conclusion: This study shows normal distribution pattern, range of SUVs, and physiological variants of 68 Ga-PSMA-11. In addition, several potential pitfalls were documented to prevent misinterpretations of the scan. Abstract : Supplemental Digital Content is available in the text.